PENGARUH VIDEO ANIMASI TUBUHKU MILIKKU TERHADAP PENGENALAN PENDIDIKAN SEKS DI TK DARUL FALAH PADANG - Cahaya Zoja, Chinta; Hazizah, Nur; Marlina, Serli; Muthie, Imam; Syafnita, Tisna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early childhood sexuality education is important to help children learn about their bodies, understand personal boundaries, and develop self-protection skills. However, its implementation still faces obstacles, particularly the limited availability of engaging and developmentally appropriate learning media. This study aims to analyze the effect of the animated video